Secure NOMA communication eavesdropped by energy harvesting-capable receiver with jamming - Ngoc, Pham Thi Dan; Son, Vo Que; Thiem, Do Dac; Son, Pham Ngoc (Journal of Computer Science and Cybernetics, 2025)
Non-orthogonal multiple access (NOMA) enables simultaneous transmissions of a huge quantity of wireless users on the same system resources (time, frequency, space), significantly improving spectral efficiency. Also, harvesting radio frequency energy for wireless communication not only saves energy resource but also makes communication greener. However, an energy harvesting-capable eavesdropper can be one of NOMA receivers, threatening security of NOMA communication. This paper secures NOMA communication eavesdropped by the energy harvesting-capable receiver by utilizing a jammer. The secrecy performance of the proposed system model is analyzed thoroughly and corroborated by computer simulations. Moreover, its secrecy performance is demonstrated to be superior to three different reference models. Furthermore, we secure the proposed system model at best by properly configuring critical system parameters.